(untitled) (Revista Contexto & Educação, 2022)
This paper aims to investigate the section of Natural Sciences in the BNCC for High School in the light of the category of labor as a curriculum organizing principle. We start from our conception, from the Historical-Critical Pedagogy, of school curriculum as the set of the core activities of the school, rendering its essential role, the transmission-assimilation of scientific, artistic and philosophical knowledge produced historically by society. The labor category is essential for the organization of the curriculum in this perspective, being possible to establish elements and principles to design curricula that go towards an omnilateral formation of individuals. Based on this framework, we discussed the organization of the Base in the area of ​​Natural Sciences and understood that the document is in line with the neoliberal logic for flexible and precarious formation, moving away from the possibility of integral formation, possible through labor.